Stability of a viscous incompressible conducting liquid layer of a cylindrical shape in an inhomogeneous temperature field and a magnetic field of a vacuum arc current through it - Andrieieva, O.L.; Borts, B.V.; Vanzha, А.F.; Korotkova, I.М.; Tkachenko, V.I. (Вопросы атомной науки и техники, 2021)
Convective mass transfer in a cylindrical viscous incompressible conductive fluid layer in an inhomogeneous temperature field and in the external magnetic field of the vacuum arc current through it is theoretically investigated in this work. For a horizontal layer of a viscous, incompressible, conducting liquid of a cylindrical shape, located in a temperature field inhomogeneous in height and in an external magnetic field of a vacuum arc current flowing through it, the original equations are written. These equations consist of linearized equations for small velocity perturbations, small deviations from the equilibrium values of temperature, pressure, and magnetic field strength. The considered boundary value problem is solved for the case of free boundaries. Comparison of the experimental data with theoretical calculations made it possible to determine the rotation velocity of the steel melt during vacuum arc melting.